Governmental Policies and Sustainable Outcomes in EU: How Innovations Change the Game? - Dmytrenko, Denys; Kuba, Ondřej (Academic Conferences and Publishing International Limited, 2024)
Environmental degradation is one of the main challenges in today's world. Impact on the environment can be reduced through the introduction of clean and more efficient technologies. And innovation plays a crucial role in this process by replacing old equipment and methods. There are different ways how researchers understand sustainable innovations and sustainable innovation ecosystems. The terms "sustainable" and "sustainable development" have become very widely used in recent years. Sustainability is crucially important for the development of regions and national economies. Existing literature on the topic of sustainable innovation ecosystems includes vague and ambiguous definitions of sustainable innovation, as well as ways to measure it. A number of studies analyse the impact of different factors on conventional innovations and eco-innovations. However, not enough research has been done on the effects of innovations on all three dimensions of sustainable innovations, which are economic, environmental, and social. The aim of the article is to define whether governmental policies that promote innovation and sustainable development lead to environmental, social, and economic improvements in the EU countries. Our study uses the Eurostat data for 27 European Union countries. The literature review will include studies on sustainable innovation ecosystems. In the second chapter, we will describe the sustainable innovation ecosystems and ways to measure the sustainable outcomes of innovations. We study sustainable innovation ecosystems on a national level. We use partial least squares structural equation modeling (PLS-SEM) to determine the influence of governmental policies on sustainable outcomes, with product and process innovation as mediating variables. Under sustainable outcomes, we mean the economic, social, and environmental improvements on a national scale. The analysis is based on applying a quantitative method with empirical data using SmartPLS software. The results demonstrated a significant direct impact of governmental policies on innovation, as well as on environmental and social outcomes. However, they showed no indirect impacts connected to innovations. The results contribute to the current state of knowledge on sustainable innovation ecosystems and give policymakers valuable insights on factors that influence such ecosystems.
Vládní politiky a udržitelné výsledky v EU: Jak inovace mění pravidla hry?
Keywords: sustainable; environmental policy; eco-innovations; governmental innovation, firms; EU; PLS-SEM, SmartPLS; udržitelnost; environmentální politika; eko-inovace; vládní inovace; firmy; EU; PLS-SEM; SmartPLS